Temporal changes in gene expression and genotype frequency of the ornithine decarboxylase gene in native silverside Basilichthys microlepidotus: Impact of wastewater reduction due to implementation of public policies. (22nd June 2020) - Veliz, David; Rojas‐Hernández, Noemi; Copaja, Sylvia V.; Vega‐Retter, Caren
Abstract: Human activity has caused a deterioration in the health and population size of riverine species; thus, public policies have been implemented to mitigate the anthropogenic impacts of water use, watercourse transformation, and pollution. We studied the Maipo River Basin, one of the most polluted with untreated wastewater in Chile, for a period of 12 years (2007‐2019). Since the implementation of new public policies, including the operation of a wastewater collector (2012), the Maipo River Basin is currently much less polluted by untreated water than before. To analyze the impact of wastewater reduction in this river basin, we studied the native silverside ( Basilichthys microlepidotus ), which inhabits both polluted and unpolluted areas of the river basin. Previous studies reported the overexpression of the ornithine decarboxylase ( odc ) gene, heterozygote deficit, and high frequency of a homozygote odc genotype in silverside populations that inhabit wastewater‐polluted sites, suggesting a phenotypic change and genotypic selection in response to pollution. Here, a population affected and another population unaffected by wastewater were studied before and after implementing the wastewater collector. The physicochemical data of water samples, changes in odc expression and microsatellite variability, and odc genotype frequencies were analyzed. The results showed physicochemical changes in the affected site before and after the operation of the wastewater collector. The microsatellite loci showed no changes in either population. The odc expression in the affected site was higher before the operation of the wastewater collector. Significant changes in the genotype frequencies of the odc gene before and after the wastewater collector operation were detected only at the affected site, wherein the homozygous dominant genotype decreased from >59% to <25%. Our results suggest that public policies aimed at mitigating aquatic pollution can indirectly affect both gene expression and genotype frequencies of important functional genes.